The Quality of Digital Radiography Images of The Sacrum Is Influenced by X-Ray Exposure Factors - Suharlim, Edwin; Kusmiati, Evie; Sugandi, Erwin Santoso; Pratama, Adhitya; Hamidah, Mila Aulia (STIKes Budi Luhur Cimahi, 2026)
Digital radiography of the sacrum requires precise adjustments of exposure parameters (kV, mA, time) to produce high-quality images while minimizing radiation exposure. This study aims to investigate how these exposure factors affect the quality of sacral images and to recommend optimal settings that align with radiation safety principles such as ALARA. By reviewing the existing literature, it was found that the modification of exposure parameters (kV, mA, time) in digital radiography is essential for achieving optimal image quality while minimizing radiation exposure. The exposure index (EI) serves as an indirect measure of the dose absorbed by the detector, thereby facilitating the implementation of the ALARA principles. Properly orienting the AEC chamber can reduce radiation dose by up to 44% without compromising image quality. Tube voltage and current adjustment enhances image contrast and sharpness. Nonetheless, inconsistent exposure methods and dependence on presets can still lead to dose creep. It is essential to train radiographers, adjust equipment settings, and set Diagnostic Reference Levels (DRLs) to enhance imaging quality and ensure patient safety. In digital radiography, factors such as tube voltage (kV), tube current (mA), and exposure time (s/mAs) significantly affect image quality and patient radiation dose. Adjusting exposure settings according to patient characteristics and exam objectives enhances image quality and reduces radiation exposure, particularly in sensitive areas like the sacrum. Technologies such as Exposure Index (EI), Automatic Exposure Control (AEC), and image analysis software facilitate an objective method that follows the ALARA principle, ensuring patient safety while optimizing diagnostic outcomes.